2018
DOI: 10.1007/s00415-018-8985-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum and cognition in progressive MS patients: functional changes beyond atrophy?

Abstract: PMS patients show cerebellar FC rearrangements that are partially independent from cerebellar structural damage, and are likely expression of a maladaptive functional rewiring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
1
26
1
Order By: Relevance
“…We found that the correlation between the FC of both cerebellar compartments and PASAT performance was influenced by the severity of cerebellar structural damage, that is, infratentorial lesion burden and cerebellar volume loss. The relationship between cerebellar structural and functional alterations has recently been investigated, 17 and revealed to be only partially independent of each other in a sample of patients with progressive MS. However, the more advanced clinical stage and more severe tissue damage in those patients could explain a different effect of structural damage on FC and cognitive impairment with respect to our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that the correlation between the FC of both cerebellar compartments and PASAT performance was influenced by the severity of cerebellar structural damage, that is, infratentorial lesion burden and cerebellar volume loss. The relationship between cerebellar structural and functional alterations has recently been investigated, 17 and revealed to be only partially independent of each other in a sample of patients with progressive MS. However, the more advanced clinical stage and more severe tissue damage in those patients could explain a different effect of structural damage on FC and cognitive impairment with respect to our results.…”
Section: Discussionmentioning
confidence: 99%
“…19 fMRI studies have shown an association between attention-task performances and increased activity in the posterior cerebellar lobe, 20 particularly between lobules VI and VII and language, memory, and executive function tasks. 17,18 Furthermore, lobule VIII was found to be activated during hand/arm and lower limb movement. 5,21…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Eventually, during the last years, the great interest regarding cerebellum involvement across different neurological diseases has been confirmed by the growing body of methodology to achieve a fine segmentation of this tiny structure (34). However, even though some newer cerebellar segmentation methods have shown higher accuracy (35) than SUIT, the latest has extensively proved to be valid in demonstrating differences between patients with MS and controls, as evidenced by a series of works published in the field (13,14,36), with the advantage of being more user friendly and less time-consuming (35). Despite these limitations, our findings indicate that regional atrophy in the cerebellum along with disruption of afferent and efferent pathways to this structure encompasses a pathological substrate of physical deficits seen in patients with MS and evaluated by measures of balance, EDSS, and 25-FWT.…”
Section: Discussionmentioning
confidence: 99%